Exploring cutting-edge innovations: highlights from the 22nd SCI/RSC Medicinal Chemistry Symposium / Nursyuhada Azzman - Azzman, Nursyuhada (UiTM Global @ Office of International Affairs, 2024)
Nursyuhada Azzman was awarded an SCI Travel Bursary to attend the 22nd SCI/RSC Medicinal Chemistry Symposium, held from the 10th to the 13th of September at Churchill College, Cambridge, United Kingdom. Upon her arrival at Storey’s Way, she was immediately captivated by the college’s charming architecture and the collegiate atmosphere. With a 50-year history of hosting meetings and conferences, Churchill College is renowned for its warm hospitality, ensuring participants have a comfortable and enjoyable experience.